Effect of testosterone treatment on cardiac biomarkers in a randomized controlled trial of men with type 2 diabetes. (23rd July 2015) - Gianatti, Emily J.; Hoermann, Rudolf; Lam, Que; Dupuis, Philippe; Zajac, Jeffrey D.; Grossmann, Mathis
Summary: Objective: To assess the effect of testosterone treatment on cardiac biomarkers in men with type 2 diabetes (T2D). Design: Randomized double‐blind, parallel, placebo‐controlled trial. Patients: Men aged 35–70 years with T2D and a total testosterone level ≤12·0 nmol/l (346 ng/dl) at high risk of cardiovascular events, median 10‐year United Kingdom Prospective Diabetes Study (UKPDS) coronary heart disease (CHD) risk 21% (IQR 16%, 27%). Eighty‐eight participants were randomly assigned to 40 weeks of intramuscular testosterone undecanoate ( n  = 45) or matching placebo ( n  = 43). Main Outcome Measures: N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) and high‐sensitivity cardiac troponin T (hs‐cTnT). Result: Testosterone treatment reduced NT‐proBNP (mean adjusted difference (MAD) in change over 40 weeks across the testosterone and placebo groups, −17·9 ng/l [95% CI −32·4, −3·5], P  = 0·047), but did not change hs‐cTnT (MAD, 0·41 ng/l (95% CI −0·56, 1·39), P  = 0·62). Six men, three in each group experienced an adverse cardiac event, displaying already higher baseline NT‐proBNP ( P  < 0·01) and hs‐cTnT levels ( P  = 0·01). At baseline, 10‐year UKPDS CHD risk was associated positively with NT‐proBNP (τ = 0·21, P  = 0·004) and hs‐cTnT (τ = 0·23, P  = 0·003) and inversely with testosterone (total testosterone τ = −0·18, P  = 0·02, calculated free testosterone τ = −0·19, P  = 0·01), but there was no significant association between testosterone and cardiac biomarkers ( P  > 0·05). Conclusions: In this trial of men with T2D and high cardiovascular risk, testosterone treatment reduced NT‐proBNP and did not change hs‐cTnT. Further studies should determine whether men with increased cardiac biomarkers prior to testosterone therapy are at higher risk of testosterone treatment‐associated adverse cardiac events.